Stigmatizing the Unhealthy. Issue 4 (December 2017) - Roberts, Jessica L.; Weeks, Elizabeth
Stigma can lead to poor health outcomes. At the same time, people who are perceived as unhealthy may experience stigma as the result of that perception. As part of a larger project examining discrimination on the basis of health status or "healthism, " we explore the role of stigma in producing disadvantage based on health status. Specifically, we look to the principles of health equality and health justice. An intervention violates health equality when it is driven by animus, which can be the result of stigma. Additionally, laws and policies offend health justice when they worsen health outcomes or they create or deepen health disparities. An intervention that produces stigma — whether intentionally or unintentionally — may offend health justice by making people worse off, in absolute or in comparative terms. Stigma-related health laws and policies can therefore be healthist in at least two ways. We therefore conclude that stigma should neither be the basis, nor the product, of efforts to improve health.